Characteristics of Using Football Elements in the Physical Education of Preschool Children - Barno Pulatovna Abdullaeva (Global Scientific Publishing, 2022)
The article discusses the use of game elements in the development of motor skills of preschool children. It is said that the use of football elements, which is a very interesting team game for children, arouses interest in children, their ability to perform exercises using football elements, good development of coordination ability
Keywords: game; dribbling; coordination; flexibility